Multi-omics molecular biomarkers and database of osteoarthritis. (5th July 2022) - Li, Jianhua; Yang, Xiaotian; Chu, Qinjie; Xie, Lingjuan; Ding, Yuwen; Xu, Xiaoxu; Timko, Michael P; Fan, Longjiang
Abstract: Osteoarthritis (OA) is the most common form of arthritis in the adult population and is a leading cause of disability. OA-related genetic loci may play an important role in clinical diagnosis and disease progression. With the rapid development of diverse technologies and omics methods, many OA-related public data sets have been accumulated. Here, we retrieved a diverse set of omics experimental results from 159 publications, including genome-wide association study, differentially expressed genes and differential methylation regions, and 2405 classified OA-related gene markers. Meanwhile, based on recent single-cell RNA-seq data from different joints, 5459 cell-type gene markers of joints were collected. The information has been integrated into an online database named OA o mics and molecular b iomarkers (OAOB). The database (http://ibi.zju.edu.cn/oaobdb/ ) provides a web server for OA marker genes, omics features and so on. To our knowledge, this is the first database of molecular biomarkers for OA.